2014
DOI: 10.4049/jimmunol.1303473
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of Peritoneally Disseminated Colon Cancer by TAP-Deficient Embryonic Stem Cell–Derived Macrophages in Allogeneic Recipients

Abstract: We established a method to generate a large quantity of myeloid lineage cells from mouse embryonic stem (ES) cells, termed ES cell–derived proliferating myeloid cell lines (ES-ML). ES-ML continuously proliferated in the presence of M-CSF and GM-CSF. ES-ML genetically modified to express an anti-HER2 (neu) mAb single-chain V region fragment reduced the number of cocultured mouse Colon-26 cancer cells expressing HER2. Stimulation of ES-ML with IFN-γ plus LPS or TNF resulted in almost complete killing of the Colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 52 publications
(57 reference statements)
2
15
0
Order By: Relevance
“…Haga and colleagues reported that allogeneic recipients of TAP-deficient mouse embryonic stem cell-derived ML cells do not develop leukemia (20). In our experiments, even in immune-deficient SCID mice, the injection of iPS-ML cells did not lead to the development of leukemia or other malignancies.…”
Section: No Evidence Of Development Of Malignancy From Human Ips-ml Isupporting
confidence: 50%
“…Haga and colleagues reported that allogeneic recipients of TAP-deficient mouse embryonic stem cell-derived ML cells do not develop leukemia (20). In our experiments, even in immune-deficient SCID mice, the injection of iPS-ML cells did not lead to the development of leukemia or other malignancies.…”
Section: No Evidence Of Development Of Malignancy From Human Ips-ml Isupporting
confidence: 50%
“…We could efficiently immortalize monocytic progenitor cells derived from human iPSCs. Moreover, these iPS-MLs could differentiate into terminally differentiated macrophages (ML-MPs), as previously reported [10,42]. ML-MPs showed enhanced cytokine secretion and therefore were deemed suitable for HTS.…”
Section: Discussionsupporting
confidence: 69%
“…These iPSC-derived Mϕs (iPSDM) are genetically highly related to their original donor cells, share striking phenotypic and functional similarities with primary human Mϕs and are amenable to genetic manipulation. Previous studies utilised iPSDMs to model rare genetic defects that impact Mϕ functions [ 10 12 ]; or investigated their utility in cellular therapies [ 13 15 ]. However, the potential of iPSDMs in host-pathogen interaction studies, especially to study human adapted pathogens, has not been fully evaluated.…”
Section: Introductionmentioning
confidence: 99%